Asseesment of the microbiological, physicochemical quality of Diyala River water, with emphasis on regulatory roles of coliform bacteria - Fahad, M. A.; Jasim, N. A.; Naif, A. I. (Regulatory Mechanisms in Biosystems, 2025)
Surface water bodies are essential sources of water for human consumption, residential use, agriculture, industrial operations, as well as for aquatic life and ecosystems. The a im of this article is to appraise the microbiological, physical, and chemical quality of the water of the Diyala River . Water samples we re collected from nine various sites along the Diyala River, during the period from winter (December ) 2023 to summer (May ) 2024. The total count of aerobic bacteria, total coliforms (TC) and fecal coliforms (FC), E. coli bacteria and physico-chemical parameters are evaluated. The results show that the water from the Diyala River is contaminated with coliform organisms in all sites. Regarding pathogens, which include bacteria Salmonella spp., Shigella spp., Klebsiella pneumoniae , Enterobacter ludwigii , and Staphylococcus spp., the results specify that there is no clear difference in abu n dance of pathogens between the two seasons. The m ean , of maximum and minimum value for temperature, electrical conduction, turbidity , BOD, DO, calcium , magnesium , n itrate concentration are all greater than the permitted values of the World Health O r ganization ( WHO ) . However, pH, chloride concentration and total dissolved solids ( TDS ) in the water samples are all within the permitted levels set by the WHO. The water quality index (WQI) and comprehensive pollution i ndex (CPI) score for all sites ind i cate that the river water quality is poor. The study indicates that the water in the study area is heavily polluted and poses significant health risks because of fecal and emerging pathogens in the samples. Therefore, there is a need for an immediate treatment for reuse.